Dynamic modification of the ETS transcription factor PEA3 by sumoylation and p300-mediated acetylation - Guo, Baoqiang (Oxford University Press, 2011)
Transcription factor activity is often controlled through the dynamic use of post-translational modifications. Two such modifications are acetylation and sumoylation, which both occur on lysine residues, providing the opportunity for cross-talk at the molecular level. Here, we focussed on the ETS-domain transcription factor PEA3 and studied the potential interplay between these two modifications. We demonstrate that PEA3 is acetylated in a p300-dependent manner. ERK MAPK pathway signalling potentiates acetylation of PEA3, and enhances its trans-activation capacity. However, the major acetylation and sumoylation events take place on the same sites in PEA3 making simultaneous modification impossible. Indeed, manipulation of either the sumoylation or acetylation pathways causes reciprocal changes in PEA3 acetylation and sumoylation respectively. However, despite the mutually exclusive nature of these modifications, both contribute to the trans-activation capacity of PEA3, implying that a dynamic series of modification events occurs during the activation process.